2001
DOI: 10.1053/rapm.2001.21437
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dipyrone versus tramadol in the management of pain after hysterectomy: A randomized, double-blind, multicenter study

Abstract: Dipyrone and tramadol showed similar efficacy for early pain relief after abdominal hysterectomy. Nausea and vomiting, possibly caused by the tramadol, occurred more frequently in those patients. In this group, the need of the antiemetic drug ondansetron was also higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
2
6
0
2
Order By: Relevance
“…Our results are consistent with other studies in which intraperitoneal administration of local anesthetic has been shown to have a modest analgesic eff ect (31,32). Of 13 clinical trials considered in a systemic review it was found that the intraperitoneal administration of bupivacaine 50-200 mg, in volumes of 10-100 ml, produced signifi cant analgesia in seven studies where supplemental analgesic consumption was signifi cantly reduced (33)(34)(35).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with other studies in which intraperitoneal administration of local anesthetic has been shown to have a modest analgesic eff ect (31,32). Of 13 clinical trials considered in a systemic review it was found that the intraperitoneal administration of bupivacaine 50-200 mg, in volumes of 10-100 ml, produced signifi cant analgesia in seven studies where supplemental analgesic consumption was signifi cantly reduced (33)(34)(35).…”
Section: Discussionsupporting
confidence: 90%
“…dieser schwerwiegenden Komplikation nach als bei vielen anderen häufig verwendeten Medikamenten [8]. Nicht zuletzt wurde das Argument "Agranulozytoserisiko" seit der Verfügbarkeit einer effizienten Therapie mit "granulozyte colony-stimulating factor" (G-CSF) [9] etwas relativiert, setzt allerdings die rechtzeitige Diagnose dieser Komplikation voraus.Nachweislich findet Metamizol in der Therapie chronischer und akuter Schmerzen weite Verbreitung und hat sich als potentes Analgetikum bewährt [16,21,27,28,32].…”
Section: Metamizolunclassified
“…Während sich Tramadol als postoperative PCA in mehreren Studien bewährt hat [14,18,20,24] und auch Metamizol schon als PCA mit Basalrate appliziert wurde [32], gibt es bis jetzt nur wenige Untersuchungen zur Kombination Tramadol und Novalgin als PCA [17,33].…”
Section: Patientenkontrollierte Analgesie Mit Metamizol Plus Opioidunclassified
“…By contrast, non-steroidal anti-inflammatory drugs (NSAIDs) and anti-pyretic analgesics are usually sufficient to provide analgesia after ambulatory surgery. 3,4 Introduced into clinical practice in 1978, tramadol is a synthetic 4-phenylpiperidine analogue of codeine with two optical isomers: one having opioid-like effects and the other antagonizing the neuronal uptake of noradrenaline and serotonin in the nerve terminals, 5 displacing serotonin stores in the spinal cord, and facilitating descending inhibitory pain pathways. 6,7 Houmes et al showed that tramadol was as effective and safe as morphine for postoperative pain relief with potential advantages of longer duration of action and limited respiratory depression.…”
Section: Introductionmentioning
confidence: 99%